Some factors affecting the storage stability of toasted anchovies (Stolephorus Commersonii) - Mateo, Rosalia Candia
The effect of the moisture content of the storage stability of toasted dilis was assessed by determining the sorption isotherms and the critical moisture content. The sorption isotherms of the product was determined trough the use of two methods; graphical interpolation and ink's weight equilibrium methods. in the determination of the critical moisture content of toasted dilis with initial moisture content of 5.4% (wet basis) was observed to have a critical moisture content of 9.1% (wet basis) to render the product rancid in odor. Based on the results of the sorption isotherm and critical moisture content, the computed maximum allowable water vapor transmission rate was 5.39 gm water/24 hr/meter square for a turnover period of 60 days. The effect of packaging material on the rate of rancidity was assessed through the peroxide test. The product was packed in a low density and high polyethylene bag stored at room temperature. The test showed a general increase in the peroxide value as storage is prolonged using both the two types of packaging material. However, the product packed in low density polyethylene bag showed much more rapid increase in peroxide than that of high density polyethylene.